2007
DOI: 10.1152/jn.00003.2007
|View full text |Cite
|
Sign up to set email alerts
|

Visual Scene Processing in Familiar and Unfamiliar Environments

Abstract: Epstein RA, Higgins JS, Jablonski K, Feiler AM. Visual scene processing in familiar and unfamiliar environments. J Neurophysiol 97: 3670 -3683, 2007. First published March 21, 2007 doi:10.1152/jn.00003.2007. Humans and animals use information obtained from the local visual scene to orient themselves in the wider world. Although neural systems involved in scene perception have been identified, the extent to which processing in these systems is affected by previous experience is unclear. We addressed this issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 64 publications
14
116
1
Order By: Relevance
“…In contrast, long-interval RS showed a greater degree of viewpoint independence, in that strong RS was observed when previously seen locations were presented again from previously unseen views. As noted in the INTRODUCTION, we observed a similar pattern of results (i.e., greater viewpoint independence for long-interval RS) in earlier experiments (Epstein et al 2005(Epstein et al , 2007a. However, these early experiments measured long-and short-interval RS in different runs during which subjects performed different tasks, so it was possible that the results could be explained by task differences rather than differences in repetition interval.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In contrast, long-interval RS showed a greater degree of viewpoint independence, in that strong RS was observed when previously seen locations were presented again from previously unseen views. As noted in the INTRODUCTION, we observed a similar pattern of results (i.e., greater viewpoint independence for long-interval RS) in earlier experiments (Epstein et al 2005(Epstein et al , 2007a. However, these early experiments measured long-and short-interval RS in different runs during which subjects performed different tasks, so it was possible that the results could be explained by task differences rather than differences in repetition interval.…”
Section: Discussionsupporting
confidence: 83%
“…These stimuli were used to examine fMRI-RS effects. In previous experiments, we found that fMRI-RS effects in the PPA were unaffected by campus familiarity (Epstein et al 2007a), so we felt confident that results obtained using these images would generalize to images of unfamiliar locations. In addition to the Penn stimuli, 144 images of the Temple University campus (3 views each of 48 different locations) were used as foil stimuli.…”
Section: Stimulimentioning
confidence: 75%
See 3 more Smart Citations